2020
DOI: 10.1002/csc2.20073
|View full text |Cite
|
Sign up to set email alerts
|

Improving photosynthetic production in rice using integrated crop management in northeast China

Abstract: Integrated crop management practices can improve rice (Oryza sativa L.) grain yield, but the effects of such practices on dry matter accumulation and photosynthetic productivity are inconsistent and not well understood. The primary objective of this study was to investigate the effects of integrated crop management practices on dry matter accumulation and redistribution, photosynthetic production, and yield of rice in northeast China. Medium‐ and high‐yielding potential japonica rice cultivars were grown using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…Meanwhile, significant mean squares due to the interaction between genotypes and seasons were significant for all studied traits indicated that genotypes behaved differently in both summer growing seasons. These results are in line with those obtained by several investigators [6,8,9,10,11,24,25,26,27].…”
Section: C-photosynthetic Parameterssupporting
confidence: 93%
“…Meanwhile, significant mean squares due to the interaction between genotypes and seasons were significant for all studied traits indicated that genotypes behaved differently in both summer growing seasons. These results are in line with those obtained by several investigators [6,8,9,10,11,24,25,26,27].…”
Section: C-photosynthetic Parameterssupporting
confidence: 93%
“…The following calculations were used: Leaf area duration (LAD) (10 4 m 2 d ha −1 ) = 1/2(LAI 1 + LAI 2 ) × ( t 2 − t 1 ) (Chu et al., 2016; Guo et al., 2020) CGR (g m −2 d −1 ) = ( W 2 − W 1 )/( t 2 − t 1 ) Rate of LAI attenuation (LAI d −1 ) = (LAI 2 − LAI 1 )/( t 2 − t 1 ) NAR (g m −2 d −1 ) = [(ln LAI 2 − ln LAI 1 )/(LAI 2 − LAI 1 )] × [( W 2 − W 1 )/( t 2 − t 1 )] (Vernon & Allison, 1963; Roy et al., 2012) Harvest index (HI) (%) = gain yield × 100/dry matter weight at maturity stage …”
Section: Methodsmentioning
confidence: 99%
“…The following calculations were used: (Chu et al, 2016;Guo et al, 2020) & Allison, 1963;Roy et al, 2012) Harvest index (HI) (%) = gain yield × 100/dry matter weight at maturity stage Grain/leaf ratio (grain cm −2 ) = number of spikelets per square meter at maturity/(10,000 × leaf area per square meter at full heading stage) (He et al, 2019) Dry matter translocation (DMT) (kg ha −1 ) = dry matter weight of stem and leaves at full heading stage − dry matter weight of stem and leaves at maturity (Liu et al, 2016;Rajinder et al, 2017) Dry matter translocation efficiency (DMTE) (%) = DMT × 100/dry matter weight of stem and leaves at full heading stage Contribution rate of DMT to grain (%) = DMT ×100/grain yield where LAI 1 and LAI 2 are the leaf area indices measured at times t 1 and t 2 , and W 1 and W 2 are the dry matter weights measured at t 1 and t 2 .…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…During in the Ninth Malaysia Plan period (2006–2010), the transformation of agriculture was focused on moving from traditional farming into modern and commercial agriculture, developing agriculture entrepreneurs, and familiarizing farmers and small landholders with all the new agronomic and modern farm management practices as contained in Good Agriculture Practice (GAP) (Guo et al 2020 ). The consolidation of small paddy farming was continued through the group farming concept in eight integrated paddy areas, and the ten metric tons per hectare (mt/ha) project was implemented throughout the period (Sarena et al 2019).…”
Section: Conceptualization and Contributing Factors: Higher Productivmentioning
confidence: 99%